The distribution of heterophilic antigens and their relationship with autoimmune diseases - Sun, Lijun; Wang, Nana; Feng, Yangmeng; Huo, Xueping; Feng, Qing; Zhao, Xiangrong; Li, Yan; Yan, Liting; Xie, Xin; Hu, Jun (Frontiers in Immunology, 2023)
Many studies have shown that microbial infections are associated with the occurrence of autoimmune diseases, but how microbial infection induces autoimmune diseases and the mechanism are still uncertain. The existence of heterophilic antigens between microorganisms and human tissues may explain part of the pathogenesis of autoimmune diseases, but the knowledge of nature and effects of heterophilic antigens are limited. In this study, monoclonal antibodies against a variety of microorganisms were prepared, and it was found that these pathogenic microorganisms induced the production of heterophilic monoclonal antibodies through heterophilic antigens.Further studies showed that the distribution of these heterophilic antigens had individual, tissue and species differences. Our results showed that heterophilic antigens exist widely between microorganisms and human body, and the heterophilic antigens carried by microorganisms may break the immune tolerance of the body through carrier effect and initiate immune response, which may be one of the important mechanisms of infection inducing autoimmune diseases.